A Drosophila Mitochondrial Complex I Deficiency Phenotype Array - Foriel, Sarah; Renkema, G. Herma; Lasarzewski, Yvonne; Berkhout, Job; Rodenburg, Richard J.; Smeitink, Jan A. M.; Beyrath, Julien; Schenck, Annette (Frontiers in Genetics, 2019)
Mitochondrial diseases are a group of rare life-threatening diseases often caused by defects in the oxidative phosphorylation system. No effective treatment is available for these disorders. Therapeutic development is hampered by the high heterogeneity in genetic, biochemical and clinical spectra of mitochondrial diseases and by limited preclinical resources to screen and identify effective treatment candidates. Alternative models of the pathology are essential to better understand mitochondrial diseases and to accelerate the development of new therapeutics. The fruit fly Drosophila melanogaster is a cost- and time-efficient model that can recapitulate a wide range of phenotypes observed in patients suffering from mitochondrial disorders. We targeted three important subunits of Complex I of the mitochondrial oxidative phosphorylation system with the flexible UAS-Gal4 system and RNA interference: NDUFS4 (ND-18), NDUFS7 (ND-20) and NDUFV1 (ND-51). Using two ubiquitous driver lines at two temperatures, we established a collection of phenotypes relevant to complex I deficiencies. Our data offer models and phenotypes with different levels of severity that can be used for future therapeutic screenings. These include qualitative phenotypes that are amenable to high-throughput drug screening and quantitative phenotypes that require more resources but are likely to have increased potential and sensitivity to show modulation by drug treatment.